DOES ENVIRONMENTAL CONSERVATION, ECONOMIC ACTIVITIES, AND THE ROLE OF GOVERNMENT AFFECT NATURAL DISASTER RISK IN EAST JAVA, INDONESIA? - DYNDA FADHLILLAH AULIA (Journal of International Conference Proceedings, 2022)
Natural disaster risks are things that need to be prioritized in relation to economic activities. The intensity of disasters is getting higher and it is necessary to know what the impact will be. Therefore, this study wants to see how much influence economic activity, population development, and the government's role have on the level of disaster risk. The panel regression model is used on secondary data from 38 districts/cities from 2015 to 2021 as a database. Based on the estimation results, there are several findings in this study: (i) increased environmental preservation and the role of the government can reduce the level of disaster risk (ii) economic activity and population density leads to an increase in disaster risk. As a result, areas with a high level of disaster risk have economic activities that need to improve prospects for a sustainable green economy and population density that causes land use change. Nevertheless, the government's role in spending is felt to be able to reduce the level of disaster risk. Of course by increasing nature conservation to reduce environmental damage.